2004
DOI: 10.1007/s00125-004-1474-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants and ACE inhibition on chemical modification of proteins and progression of nephropathy in the streptozotocin diabetic rat

Abstract: Aims/hypothesis. This study was designed to determine whether inhibition of formation of AGE and advanced lipoxidation end-products (ALE) is a mechanism of action common to a diverse group of therapeutic agents that limit the progress of diabetic nephropathy. We compared the effects of the ACE inhibitor enalapril, the antioxidant vitamin E, the thiol compound lipoic acid, and the AGE/ALE inhibitor pyridoxamine on the formation of AGE/ALE and protection against nephropathy in streptozotocin diabetic rats. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 42 publications
7
57
0
Order By: Relevance
“…This is the first application of quantitative 'gold standard' stable isotopic dilution analysis LC-MS/MS to quantify a comprehensive range of glycation, oxidation and nitration adducts in tissues, plasma and urine in experimental diabetes. Independent MS estimates of CML residues of renal glomeruli [22] and immunoassay of CML content of plasma protein of healthy control rats [23] were in agreement with estimates herein. Immunoassay of AGEs in tissue, however, has overestimated increases in experimental diabetes [4,5,24].…”
Section: Discussionsupporting
confidence: 84%
“…This is the first application of quantitative 'gold standard' stable isotopic dilution analysis LC-MS/MS to quantify a comprehensive range of glycation, oxidation and nitration adducts in tissues, plasma and urine in experimental diabetes. Independent MS estimates of CML residues of renal glomeruli [22] and immunoassay of CML content of plasma protein of healthy control rats [23] were in agreement with estimates herein. Immunoassay of AGEs in tissue, however, has overestimated increases in experimental diabetes [4,5,24].…”
Section: Discussionsupporting
confidence: 84%
“…Elevation in serum creatinine concentrations and increased urine albumin excretion in rats with streptozotocin-induced diabetes were diminished in animals treated for 30 weeks. 10,11 Pyridorin also inhibited formation of advanced glycation and lipoxidation end products and controlled plasma lipids, while limiting the loss of renal function and reducing albuminuria in Zucker rats. 12 Progression of diabetic glomerular histopathologic findings over 15 weeks of therapy decreased in db/db diabetic mice, 13 and improved albuminuria was reported in the KK-A y /Ta mouse model of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…Several preclinical studies in rat models of diabetic nephropathy have demonstrated oral Pyridorin to be efficacious in preserving renal function. [10][11][12][13][14] Two small, 24-week clinical safety trials have reported an apparent decrease in the rate of loss of renal function associated with Pyridorin treatment. 15 The purpose of our study was to determine whether 1 year of therapy with Pyridorin delayed the progressive loss of renal function in patients with type 2 diabetes mellitus and advanced nephropathy.…”
mentioning
confidence: 99%
“…Pyridoxamine also prevents ALE formation in diabetic and obese rats [36,37] through cleavage of alpha-dicarbonyl intermediates in glycoxidation and lipoxidation reactions [38]. It also effectively reduced upregulation of retinal haemoxygenase-1, which is significant as this enzyme has been previously used as a reliable marker of oxidative stress in diabetic retinopathy [25,26].…”
Section: Discussionmentioning
confidence: 99%